2020
DOI: 10.1183/23120541.00200-2020
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzaepersists in biofilm communities in a smoke-exposed ferret model of COPD

Abstract: RationaleNon-typeable Haemophilus influenzae (NTHi) is a common inhabitant of the human nasopharynx and upper airways that can cause opportunistic infections of the airway mucosa including bronchopulmonary infections in patients with chronic obstructive pulmonary disease (COPD). It is clear that opportunistic infections contribute significantly to inflammatory exacerbations of COPD; however, there remains much to be learned regarding specific host and microbial determinants of persistence and/or clearance in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…Whilst these studies provide good evidence that NTHi has the capacity to form biofilms under nutrient-rich conditions, it does not confirm whether they actually form stable, persistent biofilms within the human COPD lung. Recently, however, the ferret COPD model, involving chronic long-term exposure to cigarette smoke, has provided immunofluorescent and gene expression evidence for NTHi biofilm formation and persistence ( Hunt et al., 2020 ). Here, smoke-exposed ferret lungs, which presented characteristic histological and immunological hallmarks of COPD, showed increased NTHi aggregation and the expression of four key biofilm-associated genes, pdgX, luxS, dps and hktE , that are together involved in growth, quorum sensing, environmental stress and oxidative stress tolerance ( Hunt et al., 2020 ).…”
Section: Evidence For Nthi Biofilms In the Copd Lungmentioning
confidence: 99%
“…Whilst these studies provide good evidence that NTHi has the capacity to form biofilms under nutrient-rich conditions, it does not confirm whether they actually form stable, persistent biofilms within the human COPD lung. Recently, however, the ferret COPD model, involving chronic long-term exposure to cigarette smoke, has provided immunofluorescent and gene expression evidence for NTHi biofilm formation and persistence ( Hunt et al., 2020 ). Here, smoke-exposed ferret lungs, which presented characteristic histological and immunological hallmarks of COPD, showed increased NTHi aggregation and the expression of four key biofilm-associated genes, pdgX, luxS, dps and hktE , that are together involved in growth, quorum sensing, environmental stress and oxidative stress tolerance ( Hunt et al., 2020 ).…”
Section: Evidence For Nthi Biofilms In the Copd Lungmentioning
confidence: 99%
“…Nuclei were stained with DAPI (blue), and bacteria were stained with anti-NTHi polyclonal antibodies conjugated to Alexa 488 (green). Scale bar=50μm (Hunt et al 2020 ). Permissions to reuse images were obtained from journals and/or Copyright Clearance Centre.…”
Section: Biofilms In Chronically Infected Lungsmentioning
confidence: 99%
“…H. influenzae is the most frequent microorganism isolated from a range of PCD patients (Alanin et al 2015 ), yet it was only confirmed in vitro that H. influenzae cells are more likely to form aggregates on the PCD epithelial cells than healthy control (Walker et al 2017 ). Biofilm growth mode has long been implicated in COPD despite the lack of direct evidence, and this hypothesis was only very recently supported by the detection of H. influenzae multicellular aggregates within the airway lumen of COPD ferret (Hunt et al 2020 ). Models of chronic lung infection including the implication of microbiota and biofilms have been set up, yet many more investigations are required to consolidate the biofilm growth mode in respiratory tracts of different patients.…”
Section: Biofilms In Chronically Infected Lungsmentioning
confidence: 99%
“…RT-qPCR was performed using the Applied-Biosystems 7500 System, and oligonucleotide probes specific for pdgX, luxS, dps, hktE and omp26 (Table 2). The omp26 transcript was chosen as an endogenous control given that its expression does not vary between planktonic or biofilm mode of growth (44). The reaction mix used was the NEB Luna Universal following manufacturer's directions for cycling conditions (New England Biolabs, Ipswich, MA).…”
Section: Measurement Of Bacterial Killing By Neutrophil Extracellular Traps Derivation and Measurement Ofmentioning
confidence: 99%
“…RT-qPCR was performed using the Applied-Biosystems 7500 System, and oligonucleotide probes specific for pdgX, luxS, dps, hktE and omp26 (Table 2). The omp26 transcript was chosen as an endogenous control given that its expression does not vary between planktonic or biofilm mode of growth (44) were normalized relative to omp26 levels from the same sample. Relative quantification of gene expression was determined using the comparative CT method (2 ΔΔCT ).…”
Section: Measurement Of Bacterial Killing By Neutrophil Extracellular Traps Derivation and Measurement Ofmentioning
confidence: 99%